PENGARUH KOMPENSASI DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA KARYAWAN CENTURY 21 AURORA PRO3 PEKANBARU - Melva Susanti; Susi Hendriani; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the effect of Compensation and Quality of Work Life on Employee Performance Century 21 Aurora Pro3 Pekanbaru. The population in this study all employees totaling 42. While the sampling technique using census method. Analysis of data using multiple linear regression with SPSS version 18.00. Based on the results of data analysis known that the Compensation and the quality of work life simultaneously and partially significant effect on employee performance. The contribution of effect an independent variable is 33.5%. Based on descriptive analysis known to the employee's performance was still low, especially on indicators that responsibility by employees responsible leadership in all duty although it has been described in detail. Employees advised to further increase the responsibility to work in order to achieve maximum results. For example, by completing all the work that falls responsible in the company as well and not delay the work. Thus the performance of employees expected to increase. Managers advised to be more intense in providing clear information related to career development in the company, and can keep marketing achievements that often exceeds the target.Keyword : Compensation, Quality Work and Employee Performance.